Políticas públicas previdenciárias aplicadas à terceira idade no Estado do Pará e no Brasil e seus impactos (correlacionando RGPS e IE no contexto Pará / Brasil). - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
Several social, cultural and physical changes have occurred over the years, and these have impacted the way population aging behaves . This evolution has changed over the years the way in which the Social Security System operates. This work seeks to clarify, in the first place, the concept of the public to which this regime is submitted, moving towards the way in which the need for benefit programs and even specific laws that better fit the target audience was established. In continuity, it seeks to establish a statistical relationship on the General Social Security Registry and the Aging Index of this public. With just a textual basis it is impossible to determine whether there is a relationship between the increase in the aging rate and the General Social Security System, or if only non-financial factors contribute to this factor. Faced with this problem, the research seeks to answer this question in addition to documenting the historical burden for the arrival of Social Security as a regime known today. The dissertation in its composition seeks to dialogue its documentary base with the statistical parameters feeding these data and supporting a correlation analysis so that the research objectives are achieved. This analysis is based on confirming the possible relationship or not between two exposed variables presenting consistent characters in the presentation of data in spreadsheets and statistical graphs.
Keywords: Envelhecimento populacional; Índice de envelhecimento; Registro Geral de Previdência Social; Análise de Correlação; Seguridade social; Direitos sociais; CNPQ::CIÊNCIAS SOCIAIS APLICADAS::SEGURIDADE SOCIAL::ECONOMIA REGIONAL E URBANA; POLÍTICAS PÚBLICAS E ESTRATÉGIAS DE DESENVOLVIMENTO REGIONAL; POLÍTICAS PÚBLICAS E ESTRATÉGIAS DE DESENVOLVIMENTO REGIONAL